The fern genera Lomaria, Lomariocycas, and Parablechnum (Blechnaceae, Polypodiopsida) in southern and southeastern Brazil - Dittrich, Vinícius Antonio De Oliveira; Salino, Alexandre; Monteiro, Reinaldo; Gasper, André Luís De (Phytotaxa, 2018)
We conducted a taxonomic study of the fern genera Lomaria, Lomariocycas, and Parablechnum (Blechnaceae, Polypodiopsida) in southern and southeastern Brazil (Minas Gerais, Espírito Santo, Rio de Janeiro, São Paulo, Paraná, Santa Catarina, and Rio Grande do Sul). We recognized six species (one of Lomaria, one of Lomariocycas, and four of Parablechnum), three of which have a broad neotropical distribution and three that are endemic to Brazil. Four new records are reported for four species in different regions or states from Brazil, and a new record for Guyana. Taxonomic descriptions, synonymies, lectotypifications, a neotypification (Parablechnum usterianum), geographical distributions, and comments are given for all species occurring in the study region, as well as a key for the identification of the Brazilian species of Parablechnum.